Working experience among school-going children in the Ekumfi-Narkwa fishing and farming community, Ghana - Shaibu Bukari (Cogent Social Sciences, 2022)
This study explores the experiences of school going children who combine work and schooling in the Ekumfi-Narkwa fishing and farming community in the Central Region of Ghana. These children participate in works in their community as part of internalising their community’s norms and values, raise income and gain some skills to support their parents in a sustainable manner. The study employed a qualitative approach involving the use of in-depth interviews and participant/non-participant observations to elicit responses from the children. For these children, their tasks as fisher folks and farmers are regarded as purposeful for their everyday survival in their community. They consider the effort they put in their work as a way of reproducing inter-generational orders underpinned by strong ethical connotations. The children speak about how they gain their identities, self-esteem and skills through the work they do, the beneficial nature of the works they engage in and the ethical dimensions of engagement are emphasised. However, for their future, the children have dreams of other types of works that they think could be more fulfilling based on their level of education.